Types and Strains: Their Essential Role in Understanding Protein Aggregation in Neurodegenerative Diseases - Wemheuer, Wiebke M.; Wrede, Arne; Schulz-Schaeffer, Walter J. (Frontiers in Aging Neuroscience, 2017)
Protein misfolding and aggregation is a key event in diseases like Alzheimer's disease (AD) or Parkinson's disease (PD) and is associated with neurodegeneration. Factors that initiate protein misfolding and the role of protein aggregation in the pathophysiology of disease pose major challenges to the neuroscientific community. Interestingly, although the accumulation of the same misfolded protein, e.g. α-synuclein is detectable in all idiopathic PD patients, the disease spectrum covers a variety of different clinical presentations and disease courses. In a more recent attempt this clinical variance is being explained in analogy to prion diseases by different protein aggregate conformations. In prion diseases a relationship between protein aggregate conformation properties and the clinical disease course was shown by relating different prion types to a dementia and an ataxic disease course in Creutzfeldt-Jakob patients. This principle is currently transferred to AD, PD and other neurodegenerative diseases with protein aggregation. However, differences in protein aggregate conformation are frequently addressed as disease strains. The term “strain” also derives from prion research and evolved by adopting the virus terminology at a time when transmissible spongiform encephalopathies (later called prion diseases) were assumed to be caused by a virus. The problem is that in virus taxonomy the term "type" refers to properties of the disease agent itself and the term "strain" refers to host associated factors that interact with the disease agent and may moderately modify the clinical disease presentation. Strain factors can be discovered only after transmission and passaging of the agent in a host of a different species. The incorrect use of the terminology confuses disease agent and host factors and hampers the understanding of the pathophysiology of protein aggregate-associated neurodegenerative diseases. In this article the discoveries are reviewed that explain how the terms "type" and "strain" emerged for unconventional disease agents. This may help to avoid confusion in the terminology of protein aggregation diseases and to reflect correctly the impact of protein aggregate conformation as well as host factor contribution on different clinical variations of AD, PD and other neurodegenerative diseases.